The Implementation of a Gamification-Based Talaqqi Method to Accelerate the Qur'an Reading Ability of Grade 7G Students at SMPN 1 Karawang Barat - Muhamad Rivaldi; Muthia Hanifa Nugraha; Muhammad Rizky Akbar; M. Makbul; Romadhon (DIDAKTIKA : Jurnal Penelitian Tindakan Kelas, 2026)
This study aimed to accelerate students' Qur'anic literacy skills through the implementation of a gamification-based Talaqqi method. The research was motivated by the ability gap among Grade 7G students at SMPN 1 Karawang Barat, where most students were still at the beginner level and experienced difficulties in makharij al-huruf accuracy, consistency of mad duration, and learning motivation. This study employed Classroom Action Research (CAR) conducted in two cycles. The subjects consisted of 42 students, and the research procedures included planning, action, observation, and reflection. The data collection instruments included observation sheets and a Qur'an reading skill assessment rubric. The results showed a significant improvement in students' Qur'anic literacy. The class average score increased sharply from 58 in Cycle I to 94 in Cycle II. By the end of the study, all 42 students (100%) had reached the Proficient (Mahir) level. The integration of gamification elements such as XP (Experience Points), leaderboards through the ScoreLeader website, and badges proved effective in increasing students' motivation, confidence, and mental resilience in learning the Qur'an. This study concludes that combining the disciplined traditional Talaqqi method with modern game elements can create an interactive and effective learning ecosystem for improving the quality of students' Qur'an recitation.